2019
DOI: 10.18203/2394-6040.ijcmph20195060
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based exploratory study to assess the reasons and timings of seeking abortion services in a tertiary care hospital in Mumbai

Abstract: Background: The adoption of the Medical Termination of Pregnancy (MTP) Act has allowed for abortion on the grounds of medical and social reasons since 1972.The aim of the present study is to establish the demographic of women seeking abortion care services and to determine the role of different factors in the timing of seeking an abortion.Methods: A retrospective hospital record-based study was carried out among pregnant women seeking an MTP in a tertiary care hospital in Mumbai. The records of women seeking M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As per national family heath survey and other studies the present study also shows that majority of women presenting for abortion care (MTP-85.5% and 87.2% and treatment for other abortion-94.3% and 95.4%) reported within 12 weeks of gestation in both the calendar years. 17,18,20,25,26 However, this study found that the proportion of women seeking services for other abortion at the age of 8-10 weeks of gestation was more as compared to those for MTP. This may be due to the fact that abortion with drugs, which should be used within 9 weeks of pregnancy to be effective, was not adhered.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As per national family heath survey and other studies the present study also shows that majority of women presenting for abortion care (MTP-85.5% and 87.2% and treatment for other abortion-94.3% and 95.4%) reported within 12 weeks of gestation in both the calendar years. 17,18,20,25,26 However, this study found that the proportion of women seeking services for other abortion at the age of 8-10 weeks of gestation was more as compared to those for MTP. This may be due to the fact that abortion with drugs, which should be used within 9 weeks of pregnancy to be effective, was not adhered.…”
Section: Discussionmentioning
confidence: 66%
“…6,14,15 The present study corroborates the findings of national survey as well as other studies which have reported a higher rate of induction of abortion among older age groups. [17][18][19][20] However, the proportion of younger women (less than 18 years) seeking services for incomplete abortion was significantly more as compared to medical termination of pregnancy. Study conducted by Banerjee et al showed that women with complications of spontaneous abortion were significantly younger than women with complication due to induced abortion.…”
Section: Discussionmentioning
confidence: 99%